Usability of the SIP Protocol Within Smart Home Solutions - Hrabovsky, Jakub; Segec, Pavel; Paluch, Peter; Moravcik, Marek; Papan, Jozef (Communications - Scientific letters of the University of Zilina, 2016)
A smart home is being an important part of research due to its impact on the life of many people, who decide to try this partially known concept of building and controlling their houses. In this paper we present a little different approach to the implementation of a smart home structure and its methods in real environment. As a part of the work we specify main requirements on the architectural design, which should be considered in final solution. Our research is focused primarily on the use of open standards and tools. This approach became popular because it provides an alternative view in comparison to commercial ones, where mostly proprietary and publicly unknown protocols are used. According to this, three theoretical architectures are proposed and presented with their pros and cons. In the paper we concentrate mainly on the usage of SIP protocol and issues related to the communication between a remote user and a smart home. We are proposing two logical communication models. Each model describes the type of used SIP messages and their message flows. In addition, we consider financial aspects of simple and illustrative smart home solution, which as well pose issues to end users. Our solution offers implementation with minimal operational costs and high facility control of the smart home. The paper also includes a survey of potentially usable protocols for smart homes and the list of software (SW) and hardware (HW) components, which have been used to build a testing environment.